Cyclostratigraphy and astronomical tuning of the middle eocene terrestrial successions in the Bohai Bay Basin, Eastern China - Shi, Juye; Jin, Zhijun; Liu, Quanyou; Zhang, Rui; Huang, Zhenkai (Global and planetary change, 2019)
The Eocene is an enigmatic and interesting period due to the critical thermal events that occurred during the gradual global cooling, which have been demonstrated in the marine realm but remain poorly reported in terrestrial basins. In this study, a continuous ~404-m interval of the Middle Eocene terrestrial succession in Bohai Bay Basin, eastern China, was recovered from Well Fanye-1 in the Shengli Oilfield. This interval provides a unique record that can be used to better clarify the terrestrial sedimentary responses to astronomically forced climate changes, especially the Middle Eocene Climatic Optimum (MECO). Here, a high-resolution cyclostratigraphic framework from the lower third member (Es3l) to the upper fourth chun member (Es4cu) of the Shahejie Formation (Middle Eocene) was constructed by using magnetic susceptibility (MS) as a palaeoenvironmental proxy, in association with new paleomagnetic data. Power spectral analysis of the MS series reveal that the wavelength ratios of stratigraphic cycles are ~43.1–25:15.3–7.5:4.5–3:2.2–1.4, consistent with the period ratios of astronomical cycles. Moreover, a high-resolution astronomical time scale (ATS) for Well Fanye-1 was established by tuning the MS curves to the astronomical solution in combination with the magnetic stratigraphic framework. The method for establishing a high-resolution ATS with magnetostratigraphy and cyclostratigraphy was well applied in Well Fanye-1, making it possible to recalculate the ages in the Jiyang Depression. Finally, the terrestrial record across the MECO event was constructed and characterized based on the widespread “interbedded” argillaceous limestone. The resulting record is consistent with the time frame based on marine records and highlights the apparently primary role of the MECO event in shaping Asian paleoenvironments. [Display omitted] •A cyclostratigraphic analysis of a middle Eocene lacustrine succession from the Bohai Bay Basin in eastern China was accomplished.•The method to establish an ATS with magnetostratigraphy and cyclostratigraphy is well applied in Well Fanye-1.•The terrestrial record across the MECO event was constructed and characterized based on the “interbedded” argillaceous limestone.